2009
DOI: 10.1590/s1413-86702009000200006
|View full text |Cite
|
Sign up to set email alerts
|

Ineffectiveness for infants of immunization of mothers with pneumococcal capsular polysaccharide vaccine during pregnancy

Abstract: Pneumococcal (Pnc) carriage is associated with pneumococcal diseases. Breast feeding and maternal vaccination may be a useful approach to prevent pneumococcal infection in young infants. We examined the risk of Pnc carriage by infants at six months of age after pneumococcal polysaccharide vaccination of pregnant women. We selected 139 pregnant woman. The woman were randomly allocated to receive 23-valent polysaccharide vaccines during pregnancy (Group 1) after pregnancy (Group 2) or not receive any vaccine (Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…A study undertaken in Bangladesh reported that 50 percent of the infants were colonized with pneumococcus by three months and three-quarters by six months but these figures were unaffected by maternal polysaccharide vaccination [43]. A Brazilian study reported that around 17 percent of infants were colonized at 3 months and by six months between 26 and 27 percent had carried the bacteria although again maternal vaccination did not alter the total pneumococcal carriage rates and serotype specific carriage was not reported [51] Pneumococcal disease outcomes (including meningitis, pneumonia, otitis media and mortality from acute lower respiratory infections) were reported in three trials but no significant differences were detected reflecting the small sample sizes and hence low event rates in each case [46,47,52].…”
Section: Maternal Vaccinationmentioning
confidence: 98%
“…A study undertaken in Bangladesh reported that 50 percent of the infants were colonized with pneumococcus by three months and three-quarters by six months but these figures were unaffected by maternal polysaccharide vaccination [43]. A Brazilian study reported that around 17 percent of infants were colonized at 3 months and by six months between 26 and 27 percent had carried the bacteria although again maternal vaccination did not alter the total pneumococcal carriage rates and serotype specific carriage was not reported [51] Pneumococcal disease outcomes (including meningitis, pneumonia, otitis media and mortality from acute lower respiratory infections) were reported in three trials but no significant differences were detected reflecting the small sample sizes and hence low event rates in each case [46,47,52].…”
Section: Maternal Vaccinationmentioning
confidence: 98%
“…Most of the studies of the impact of maternal immunization on infants have used PPV which, with some exceptions [26], has been found to be safe and immunogenic in pregnant women in the USA, Papua New Guinea, Bangladesh and the Gambia [27–29], and is currently recommended for pregnant women belonging to risk groups for pneumococcal disease in at least the USA and Australia [30]. In line with the results reported by other authors [31,32], Holmlund et al.…”
Section: Pneumococcal Vaccinesmentioning
confidence: 99%
“…Most of the studies of the impact of maternal immunization on infants have used PPV which, with some exceptions [26], has been found to be safe and immunogenic in pregnant women in the USA, Papua New Guinea, Bangladesh and the Gambia [27][28][29], and is currently recommended for pregnant women belonging to risk groups for pneumococcal disease in at least the USA and Australia [30]. In line with the results reported by other authors [31,32], Holmlund et al [33] have recently shown that vaccinating mothers during pregnancy gives newborns significantly higher serum anti-polysaccharide antibody concentrations for the first 4-5 months of life than those observed in the infants of unvaccinated mothers.…”
Section: Pneumococcal Vaccinesmentioning
confidence: 99%
“…However, maternal pneumococcal polysaccharide vaccination during pregnancy did not affect pneumococcal carriage in breast-fed infants at 6 months of age. 65 Shahid et al 66 assessed pneumococcal immunization during pregnancy and determined the amount of pneumococcal antibody transmitted to the infants in serum and milk; they reported that the half-life of the breast milk IgA antibodies for pneumococcal serotype 19F (passively acquired), but not for type 6B, were significantly higher in vaccine recipients up to five months after delivery.…”
Section: Maternal Immune Challenges (Vaccines or Pathogen Exposure) Dmentioning
confidence: 99%